Hepatitis B-related awareness among health care workers in Belgrade, Serbia - Kisić Tepavčević, Darija; Kanazir, Milena; Marić, Gorica; Zarić, Milica; Lončarević, Goranka; Gazibara, Tatjana; Maksimović, Nataša; Pekmezović, Tatjana (Vojnosanitetski pregled, 2021)
Background/Aim. Despite the availability of safe and effective vaccine since 1982, hepatitis B virus (HBV) infection still remains a major occupational disease among health care workers (HCWs) worldwide. The aim of this study was to estimate the level of knowledge regarding HBV among HCWs in Serbia. Methods. A random sample of 352 HCWs, stratified by occupation, was selected from the list of employees in the Clinical Centre of Serbia during December 2015. Anonymous questionnaire was used in data collection. Data were statistically assessed. Results. The mean HBV knowledge score was 22.9 ± 4.8 (out of maximum 30). Better knowledge score correlated with higher education attainment (ρ = 0.377; p < 0.001), younger age (ρ = -0.113; p = 0.034) and less working experience (ρ=-0.127; p = 0.017). We observed that those HCWs who were previously vaccinated against hepatitis B demonstrated statistically significantly higher knowledge level (t = 5.656, p < 0.001) compared to HCWs who were not vaccinated (23.9 ± 3.7 vs. 20.9 ± 5.8, respectively). Conclusion. We found poor level of knowledge on some aspects of HBV infection among HCWs in Serbia. Tailoring of education campaigns in this high-risk exposure group is necessary. Education intervention should focus on change of attitudes and behaviour modification to ensure safe and responsible health care environment.